1-Benzyl-3-[(dimethylamino)methylene]-4-phenyl-1H-1,5-benzodiazepine-2(3H)-thione - Ballo, Daouda (International Union of Crystallography, 2010)
The title compound, C(25)H(23)N(3)S, crystallizes with two independent molecules in the asymmetric unit. The seven-membered fused-ring adopts a boat conformation, with the two bridgehead C atoms representing the stern and the C atom bearing the exocyclic double bond the prow.